Reassessing Bassam Tibi’s critique of the Islamic purification movement: A hadith and Salafi tradition perspective - Hadi, Sofyan; Sori, Sofian; Iskandar, Amin (Jurnal Iman dan Spiritualitas, 2025)
This article critically examines Bassam Tibi's conception of contemporary Islamic purification movements in his work "Islamism and Islam" using hadith criticism methodology and the Salaf scholars' tradition as analytical frameworks. The research identifies three fundamental problems in Tibi's thought construction based on manhaj an-naqd al-hadith and the Salaf scholars' critical methodology. First, methodological inconsistencies in understanding the concepts of bid'ah and purification, which contradict the basic principles established in authentic hadiths concerning renewal (tajdid) and purification (tasfiyah). Second, epistemological errors in comprehending the relationship between revealed texts (nass) and ijtihad, which deviate from the Salaf scholars' methodology in understanding the dynamic interaction between the two. Third, secularist bias in analyzing Islamic purification movements that contradicts the Salaf approach in understanding the concept of asalah (authenticity). This research argues that while Tibi raises important issues about extremism in contemporary purification movements, his analysis fundamentally contradicts the hadith criticism methodology and Salaf scholars' tradition. The article concludes that a more balanced approach is needed in examining Islamic purification movements, one that integrates hadith criticism methodology and the Salaf scholars' approach while maintaining a critical stance toward contemporary deviations in Islamic purification practices.